2022
DOI: 10.1111/vsu.13777
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo biomechanical evaluation of polyester and polyblend suture techniques to perform equine laryngoplasty

Abstract: To validate the use of a polyblend tape suture in equine laryngoplasty (PL).Study design: Experimental study. Animals: Thirty-two cadaveric larynges.Methods: Each larynx was randomly assigned to 1 of 4 groups: PL with polyblend tape suture (TigerTape), without (TT) or with a cannula (TTC) in the muscular process of the arytenoid cartilage, and PL with polyester suture (Ethibond), without (EB) or with a cannula (EBC). Construct stiffness, total migration, creep, and drift values were measured after 3000 cycles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…6,7,[17][18][19] Implications of needle selection for the muscular process were evident in the present study, with a more heterogeneous distribution of selection evident for the muscular process of the arytenoid cartilage compared to that reported for the cricoid cartilage. The published literature indicates multiple potential benefits from the use of an implant (for example a metallic screw or toggle) as part of the arytenoid-prosthesis construct; [6][7][8][9] however, it is evident that in the current study most surgeons still use a simple, single loop for placement of the prosthesis at the muscular process. The findings of the current study indicate that biomechanics is unlikely to be the only attribute considered by surgeons when selecting construct types in a clinical context.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…6,7,[17][18][19] Implications of needle selection for the muscular process were evident in the present study, with a more heterogeneous distribution of selection evident for the muscular process of the arytenoid cartilage compared to that reported for the cricoid cartilage. The published literature indicates multiple potential benefits from the use of an implant (for example a metallic screw or toggle) as part of the arytenoid-prosthesis construct; [6][7][8][9] however, it is evident that in the current study most surgeons still use a simple, single loop for placement of the prosthesis at the muscular process. The findings of the current study indicate that biomechanics is unlikely to be the only attribute considered by surgeons when selecting construct types in a clinical context.…”
Section: Discussionmentioning
confidence: 85%
“…Biomechanical research has also been important in relation to the selection of appropriate prosthesis materials. 9 , 13 , 14 , 15 The original description of the prosthetic laryngoplasty in 1970 utilized a polyurethane suture, 1 although a later survey in 1993 indicated that surgeons at that time elected to use a variety of other prosthesis materials. 4 Subsequent literature has continued to demonstrate the use of a large variety of different prosthesis materials in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations